LITERATUR REVIEW: KECEMASAN IBU DENGAN PERSALINAN LAMA (PROLONG) KALA 1 FASE AKTIF: LITERATUR REVIEW: MATERNAL ANXIETY WITH PROLONGE MOTHER DURING ACTIVE PHASE I - Susanti Tria Jaya; Luluk Susiloningtyas; Elisa Nofyanti (Stikes Pamenang, 2023)
Abstrak Pendahuluan: Kecemasan ibu bersalin pada proses persalinan akan berpengaruh terhadap lamanya durasi persalinan. Angka kecemasan pada ibu hamil dalam menghadapi persalinan masih cukup tinggi sekitar 30% ibu hamil mengalami kecemasan menghadapi persalinan. Kecemasan menghadapi persalinan umumnya dialami ibu hamil menjelang persalinan adalah suatu hal yang fisiologis, tetapi jika tidak teratasi akan berdampak pada proses persalinan. Tujuan literature review ini adalah untuk mengetahui Kecemasan selama Persalinan Lama (Prolong) Kala 1 Fase Aktif. Metodologi: Literatur review ini menggunakan metodologi berdasarkan sistematika dan pedoman review. Hasil: Kecemasan dengan terjadinya persalinan lama (Prolong) pada ibu bersalin kala 1 fase aktif, mayoritas penelitian menyatakan bahwa ibu bersalin mengalami kecemasan dalam mengalami kecemasan. Diskusi: Berdasarkan hasil literature review tersebut, bidan hendaknya lebih memperhatikan kondisi psikologis ibu yang mengalami kecemasan dalam menghadapi persalinan agar faktor psikologi persalinan dapat mempengaruhi kemajuan dilatasi serviks agar segera terjadi pembukaan lengkap sehingga dapat mencegah kejadian persalinan lama kala I fase Aktif Kata kunci : kecemasan, persalinan lama, kala 1 fase aktif AbstractIntroduction: Labor is a process of opening and thinning the cervix and the fetusdescends into the birth canal. The aim of this study was to determine the relationship oflevel of anxiety with the occurrence of prolonged labor (prolongation) at the time ofdelivery active phase 1 Method: The design of this study was cross sectional research. Accidental sampling technique with aIntroduction: A mother's anxiety during the birthing process will influence the length of labor. The level of anxiety among pregnant women regarding childbirth is still quite high, around 30% of pregnant women experience anxiety regarding childbirth. Anxiety about childbirth is generally experienced by pregnant women before delivery is a physiological thing, but if it is not resolved it will have an impact on the birth process. The purpose of this literature review is to determine Anxiety during Prolonged Labor in the 1st Stage of the Active Phase. Methodology: This literature review uses a methodology based on systematics and review guidelines. Results: Anxiety about the occurrence of long labor (Prolong) in mothers giving birth during the 1st active phase, the majority of research states that mothers in labor experience anxiety when experiencing anxiety. Discussion: Based on the results of the literature review, midwives should pay more attention to the psychological condition of mothers who experience anxiety in facing labor so that the psychological factors of labor can influence the progress of cervical dilatation so that complete opening occurs immediately so that it can prevent long labor during the first active phase. Keywords: anxiety, long labor, active phase 1st stage